Volatility Spillovers across Developed/Developing Markets: The Case of India - Adrangi, Bahram; Chatrath, Arjun; Raffiee, Kambiz; Sharma, Nitin (Indian Journal of Finance, 2013)
The present research paper investigates the daily volatility spillovers between Standard and Poor’s 500, Nikkei, and India’s Nifty index between the time period from 2000 - 2009. We find that the price series exhibit nonlinear dependencies, inconsistent with chaotic structure. Bivariate GARCH estimations with volume controls indicate multi-directional spillovers. Finding evidence of asymmetric market responses to shocks, we propose and estimate asymmetric bivariate EGARCH models. We find transmissions to be asymmetric whereby positive and negative shocks have an unequal impact on the volatility of the other market. While the relationship between the developed markets is strong, the influence of the less developed Indian market is also apparent.